Financial Digitalization Knowledge for Investment and MSMEs Funding Access - Utami, Wiwik; Akbar, Taufik; bin Rahmad, Khozaeni; Pitchay, Anwar Allah; Agustin, Andhika Permana; Alvanny, Laura Vidya (MOVE: Journal of Community Service and Engagement, 2026)
The urgency of this community service program lies in the fact that Micro, Small, and Medium Enterprises (MSMEs) is the backbone of the Indonesian economy—contributing over 60% to national GDP. As financial technology (fintech) continues to evolve, the gap between opportunity and MSMEs’ readiness is widening. Without timely intervention, many MSMEs risk being excluded from the benefits of Indonesia’s growing digital economy, limiting their growth and long-term resilience. This   community service was designed to raise awareness of financial digitalization among MSMEs and Indonesian migrant workers in Penang, Malaysia. The objective is to enhance understanding of digital bookkeeping, electronic payments (QRIS, e-wallets), fintech-based financing (P2P lending, crowdfunding), and basic investment access. By increasing awareness, the program aims to strengthen MSMEs' financial transparency, digital readiness, and long-term business prospects. The sessions were designed to be interactive and accessible for participants with limited prior exposure to fintech tools. Results of the program engaged 35 MSME participants. Evaluation results showed that 91% improved their awareness of digital  knowledge, 86% gained understanding of QRIS and e-wallets, and 74% expressed interest in fintech funding options.  Contribution of the program       enhances MSMEs’ preparedness for digital financial inclusion, supports national goals of economic digitalization, and aligns with higher education’s mandate to deliver measurable social impact through community service.